Experience report: the nursing student's perception of the surgical patient's anxiety and fear (Research, Society and Development, 2020)
Objective: to report the experience of nursing students in a surgical center in Manaus, regarding the development of anxiety in patients in the perioperative period. Method: The study is an experience report, carried out in a Surgical Center and Anesthetic Recovery Room of a reference hospital in general surgery in the north of the city of Manaus, from August 2019 to June 2020. Result: In this context, anxiety and fear are feelings present in all patients who will undergo a surgical procedure, these feelings being included in the second priority level that involve sociocultural, spiritual and psychological security needs, thus corroborating with the theory of human needs basic. Conclusion: In this way, nursing assumes responsibilities and natural interventions to care for these patients, as they are the closest professional on a daily basis during the hospitalization period, which requires extensive knowledge that goes beyond their professional competence, seeking to make that moment of uncertainty in a more enlightened, reliable and comfortable environment for the patient.